Analisis Kepuasan Pengguna Aplikasi Canva Menggunakan Metode EUCS (End User Computing Satisfaction) Di Kota Jambi - Anggun Rahmadha Cevi; Davina Naja Sabila; Bagas Alif Armando Nasution; Alfi Alifio Liputo; Ulfa Khaira; Rahmad Ashar; Niko Akbar (Technology and Informatics Insight Journal, 2026)
Canva is a widely used graphic design platform that supports academic activities, work and creativity. The high level of Canva usage needs to be balanced by an assessment of user satisfaction to determine the extent to which the application meets users’ needs. This study aims to analyse the level of user satisfaction with the Canva application in Jambi City using the End User Computing Satisfaction (EUCS) method. The study employs a quantitative approach with purposive sampling and involves 150 Canva users in Jambi City. Data were collected via an online questionnaire and analysed using SmartPLS 4. The results indicate that the model explains 71.3% of user satisfaction. The variables ‘Content’, ‘Ease of Use’ and ‘Timeliness’ have a positive and significant influence on user satisfaction, whilst ‘Accuracy’ and ‘Format’ do not have a significant influence. ‘Content’ is the most dominant factor influencing user satisfaction with the Canva application in Jambi City.